Comprehensive Survey of PID Controller Design for the Inverted Pendulum - Kuczmann, Miklós (Acta Technica Jaurinensis, 2019)
The survey shows the detailed PID controller design how to stabilize the inclination angle as well as the horizontal movement of an inverted pendulum on a cart system step by step. Pendulum model is based on Euler-Lagrange modeling, and the nonlinear state space model is linearized in the unstable upward position. Controller design is performed by applying the transfer function description. The pendulum has been inserted into a virtual reality laboratory, which is suitable to use in model based control teaching.